Property development - Reed, Richard, 1963- (New York : Routledge, 2021)
"This fully revised 7th edition of Property Development has been completely updated to reflect ongoing changes in the property field and maintain the direct relevance of the text to all stakeholders involved in studying the property development process"--
Revised edition of Property development, 2015.
Includes bibliographical references and index.
Keywords: Real estate development -- Great Britain; Real property -- Valuation -- Great Britain; Real estate investment -- Great Britain; Real property -- Great Britain